Characterization of Some Stilbenoids Extracted from Two Cultivars of Lambrusco—Vitis vinifera Species: An Opportunity to Valorize Pruning Canes for a More Sustainable Viticulture - Veronica D’Eusanio; Francesco Genua; Andrea Marchetti; Lorenzo Morelli; Lorenzo Tassi (Molecules, 2023)
Pruning canes from grape vines are valuable byproducts that contain resveratrol and other health-boosting stilbenoids. This study aimed to assess the effect of roasting temperature on the stilbenoid content of vine canes by comparing two Vitis vinifera cultivars, Lambrusco Ancellotta and Salamino. Samples were collected during different phases of the vine plant cycle. One set was collected in September after the grape harvest and was air-dried and analyzed. A second set was obtained during vine pruning in February and evaluated immediately after collection. The main stilbenoid identified in each sample was resveratrol (~100–2500 mg/kg), with significant levels of viniferin (~100–600 mg/kg) and piceatannol (~0–400 mg/kg). Their contents decreased with increasing roasting temperature and residence time on the plant. This study provides valuable insights into the use of vine canes in a novel and efficient manner, which could potentially benefit different industries. One potential use involves the roasted cane chips to accelerate the aging of vinegars and alcoholic beverages. This method is more efficient and cost-effective than traditional aging, which is slow and unfavorable from an industrial perspective. Furthermore, incorporating vine canes into maturation processes reduces viticulture waste and enhances the final products with health-promoting molecules, such as resveratrol.